The Hoffmann reflex is different in men and women. Issue 4 (7th March 2018) - Hoffman, Mark; Norcross, Marc; Johnson, Sam
Abstract : To compare the maximum Hoffmann reflex (H-reflex) and the maximum M-wave (H : M) ratio of the H-reflex in men and women when all participants showed similar saliva levels of estradiol and progesterone. This is a cohort design study involving healthy men and women with a mean age of 22.4±3.4 years. The H : M ratio of the H-reflex was assessed in women and men at a point in time when naturally occurring levels of estradiol and progesterone were similar. The female participants had a significantly higher H : M ratio compared with the male participants, whereas no differences in the saliva levels of progesterone and estradiol were detected. This is the first study to report differences between women and men in the H : M ratio of the H-reflex. An additional novel aspect of this study is that the assessments were performed when the levels of neuroactive sex hormones (estradiol and progesterone) were similar in all participants.